Does depression increase the risk of stroke in patients with rheumatoid arthritis? A population-based cohort study. Issue 4 (22nd June 2017) - Tsai, Tzung-Yi; Lu, Ming-Chi; Livneh, Hanoch; Chiu, Shan-Yun; Lai, Ning-Sheng; Guo, How-Ran
Abstract : Objectives: Comorbid depression is common and undertreated in patients with rheumatoid arthritis (RA). It remains uncertain whether comorbid depression provoked the risk of poor clinical outcome, stroke in particular, among patients with RA. This work aimed to determine if depression onset during the treatment process increases stroke risk for patients with RA as compared with those with (1) neither RA nor depression, (2) RA only and (3) depression only. Design: A nationwide, population-based cohort study. Setting: Taiwan's Longitudinal Health Insurance Database. Participants: We identified 8045 subjects with a newly diagnosed RA between 1997 and 2010, together with 32 600 subjects without RA matched by age, gender and index date. All subjects were further divided into four groups based on whether they were diagnosed with comorbid depression during the follow-up period. Main outcome measure: The incidence rate and HR for incident stroke were estimated by the end of 2012 using Cox proportional hazard regression. Results: We discovered that patients with RA with the comorbid depression exhibited the highest risk of stroke, with an adjusted HR of 2.18 (95% CI 1.87 to 2.54). Those with RA only or those with depression only still had the higher risk of stroke by 43% and 57% as compared with subjects without either condition. Multivariate analysis showed RA subjects who were male or older, incurred the onset of depression, or had comorbidities such as hypertension, diabetes as well as heart disease, had a greater risk of stroke. Conclusions: This study cleared up the significant association between RA and the subsequent risk of stroke, and further highlighted that the onset of depression within the treatment process may increase stroke risk for RA subjects. Findings could assist healthcare providers to pinpoint individuals with RA with a higher predisposition of stroke, which could facilitate the provision of appropriate rehabilitation.